Combination Therapy of Chemoembolization and Hepatic Arterial Infusion Chemotherapy in Hepatocellular Carcinoma with Portal Vein Tumor Thrombosis Compared with Chemoembolization Alone: A Propensity Score-Matched Analysis. (15th July 2021) - Liu, Bao-Jiang; Gao, Song; Zhu, Xu; Guo, Jian-Hai; Kou, Fu-Xin; Liu, Shao-Xing; Zhang, Xin; Wang, Xiao-Dong; Cao, Guang; Chen, Hui; Liu, Peng; Zhu, Lin-Zhong; et al.
Abstract : Background . Survival of patients with portal vein tumor thrombosis (PVTT) is extremely poor; transarterial chemoembolization (TACE) is a treatment for patients with HCC and PVTT. Some studies showed that hepatic arterial infusion chemotherapy (HAIC) might improve the survival of HCC with PVTT. There were few researches of combining TACE with HAIC for patients with HCC and PVTT. Aim . This study was aimed at comparing overall survival (OS) and progression-free survival (PFS) following treatment with conventional transarterial chemoembolization plus hepatic arterial infusion chemotherapy (cTACE-HAIC) or conventional transarterial chemoembolization (cTACE) alone in patients with hepatocellular carcinoma (HCC) and portal vein tumor thrombosis (PVTT). Methods . From January 2011 to December 2016, 155 patients with HCC and PVTT who received cTACE-HAIC (cTACE-HAIC group) (n = 86 ) or cTACE alone (cTACE group) (n = 69 ) were retrospectively evaluated. Propensity score matching (PSM) reduced the confounding bias and yielded 60 matched patient pairs. The tumors' responses were evaluated using the modified response evaluation criteria in solid tumors (mRECIST). OS and PFS of groups were compared using the Kaplan-Meier method, log-rank test, and Cox proportional hazard regression models. Results . The median follow-up duration was 93 months (range: 1–93 months). The cTACE-HAIC group's OS (9.0 months) and PFS (6.0 months) were significantly longer than the cTACE group's OS (5.0 months) and PFS (2.0 months) (p = 0.018 and p = 0.045, respectively) in the matched cohort. Multivariate analyses showed that cTACE-HAIC was independently associated with OS (hazard ratio (HR) 0.602, p = 0.010 ) and PFS (HR 0.66, p = 0.038 ). The matched groups did not differ regarding grade 3 or 4 adverse events. Conclusion . cTACE-HAIC was superior to cTACE alone regarding OS and PFS in patients with HCC and PVTT. Treatment-associated toxicities were generally well tolerated.